2016
DOI: 10.1155/2016/7628761
|View full text |Cite
|
Sign up to set email alerts
|

A Method for the Simultaneous Cleansing of H2S and SO2

Abstract: A method for the simultaneous electrochemical purification of hydrogen sulfide and sulfur dioxide from sea water or industrial wastes is proposed. Fundamentally the method is based on the electrochemical affinity of the pair H2S and SO2. The reactions (oxidation of H2S and reduction of SO2) proceed on а proper catalyst in a flow reactor, without an external power by electrochemical means. The partial curves of oxidation of H2S and reduction of SO2have been studied electrochemically on different catalysts. Foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Cr2O7 2-+ 6 Cr 2+ + 14 H + → 8 Cr 3+ + 7 H2O 2 Cr 3+ + 3 MnO2 + 2 H2O → 2 HCrO4 -+ 3 Mn 2+ + 2 H + 2 HCrO4 -→ Cr2O7 2-+ H2O (Liang et al, 2021;Szabó et al, 2018;Topich et al, 2004, p. 59 (Kalmus, 1914;Sakka, 1991;马 et al, 2003, p. 480) Group 10 7 NiS2 + Ni3S2 → 4 NiS 3 NiS + H2 → Ni3S2 + H2S (Delafosse et al, 1962;Delafosse and Barret, 1961) Group 11 9 Cu + Cu 2+ → 2 Cu + Cu + + Fe 3+ → Cu 2+ + Fe 2+ (Bjergbakke et al, 1976;Ciavatta et al, 1980;Orth et al, 1989) Group 12 7 Hg + Hg 2+ → Hg2 2+ Hg2 2+ + 2 Fe 2+ → 2 Hg + 2 Fe 3+ (Kozin and Hansen, 2013;Raposo et al, 2000) Group 13 14 2 B2O3 + 2 B → 3 B2O2 B2O2 + 2 H2 → 2 B + H2O (Inghram et al, 1956;Sommer et al, 1963;Wang et al, 2008) Group 14 22 C + CO2 → 2 CO CO + FeO → Fe + CO2 (Wilson and Bremner, 1948) Group 15 25 HNO2 + HNO3 → 2 NO2 + H2O 2 NO2 + Cu + 2 H + → 2 HNO2 + Cu 2+ (Abd El Aal et al, 1992;Evans, 1944) Group 16 32 SO2 + 2 H2S → 3 S + 2 H2O S + O2 → SO2 (Patnaik, 2003, p. 892;Steudel, 2003;Uzun et al, 2016) Group 17 21 HCl + HOCl → Cl2 + H2O Cl2 + H2 → 2 HCl (Lister, 1952;Patnaik, 2003, p. 210) Group 18 4 XeF4 + Xe → 2 XeF2 XeF2 + F2 → XeF4 (Claassen et al, 1962;Weinstock et al, 1966;马 et al, 2003, p. 332) In addition, the use of the term "comproportionation" in published literature is sometimes not necessarily associated with redox reactions following the pattern shown in Fig. 1A, but only emphasizes a specific stoichiometric relationship (IUPAC, 1997b…”
Section: Count Of Compacs Representative Compac Referencesmentioning
confidence: 99%
“…Cr2O7 2-+ 6 Cr 2+ + 14 H + → 8 Cr 3+ + 7 H2O 2 Cr 3+ + 3 MnO2 + 2 H2O → 2 HCrO4 -+ 3 Mn 2+ + 2 H + 2 HCrO4 -→ Cr2O7 2-+ H2O (Liang et al, 2021;Szabó et al, 2018;Topich et al, 2004, p. 59 (Kalmus, 1914;Sakka, 1991;马 et al, 2003, p. 480) Group 10 7 NiS2 + Ni3S2 → 4 NiS 3 NiS + H2 → Ni3S2 + H2S (Delafosse et al, 1962;Delafosse and Barret, 1961) Group 11 9 Cu + Cu 2+ → 2 Cu + Cu + + Fe 3+ → Cu 2+ + Fe 2+ (Bjergbakke et al, 1976;Ciavatta et al, 1980;Orth et al, 1989) Group 12 7 Hg + Hg 2+ → Hg2 2+ Hg2 2+ + 2 Fe 2+ → 2 Hg + 2 Fe 3+ (Kozin and Hansen, 2013;Raposo et al, 2000) Group 13 14 2 B2O3 + 2 B → 3 B2O2 B2O2 + 2 H2 → 2 B + H2O (Inghram et al, 1956;Sommer et al, 1963;Wang et al, 2008) Group 14 22 C + CO2 → 2 CO CO + FeO → Fe + CO2 (Wilson and Bremner, 1948) Group 15 25 HNO2 + HNO3 → 2 NO2 + H2O 2 NO2 + Cu + 2 H + → 2 HNO2 + Cu 2+ (Abd El Aal et al, 1992;Evans, 1944) Group 16 32 SO2 + 2 H2S → 3 S + 2 H2O S + O2 → SO2 (Patnaik, 2003, p. 892;Steudel, 2003;Uzun et al, 2016) Group 17 21 HCl + HOCl → Cl2 + H2O Cl2 + H2 → 2 HCl (Lister, 1952;Patnaik, 2003, p. 210) Group 18 4 XeF4 + Xe → 2 XeF2 XeF2 + F2 → XeF4 (Claassen et al, 1962;Weinstock et al, 1966;马 et al, 2003, p. 332) In addition, the use of the term "comproportionation" in published literature is sometimes not necessarily associated with redox reactions following the pattern shown in Fig. 1A, but only emphasizes a specific stoichiometric relationship (IUPAC, 1997b…”
Section: Count Of Compacs Representative Compac Referencesmentioning
confidence: 99%
“…It has been shown that atmospheric SO 2 has a detrimental effect, not only on the environment but also human life [5,6]. With more countries and governments enforcing limitations on industry to reduce SO 2 emissions [5][6][7], new technologies are emerging for either the capture [8] or reutilisation of SO 2 [9,10].…”
Section: Introductionmentioning
confidence: 99%